2019
DOI: 10.1177/1468087419889833
|View full text |Cite
|
Sign up to set email alerts
|

Efficient light-duty engine using turbulent jet ignition of lean methane mixtures

Abstract: Diesel engines use diffusion-controlled combustion of a high-reactivity fuel and offer high efficiencies because they combine lean combustion with a high compression ratio. For low-reactivity fuels such as gasoline or natural gas, premixed combustion is used, which leads to lower efficiency levels as usually stoichiometric combustion is combined with lower compression ratios. Trying to apply diesel-like process parameters to low-reactivity fuels inevitably leads to problems with classical spark ignition system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 67 publications
1
11
0
Order By: Relevance
“…Attard et al 7,8 have demonstrated the capability of the PCI concept, increasing the air dilution limit above = 2.0 while maintaining very high levels of engine e ciency. This has been confirmed in more recent studies 9,10 .…”
Section: Introductionsupporting
confidence: 79%
“…Attard et al 7,8 have demonstrated the capability of the PCI concept, increasing the air dilution limit above = 2.0 while maintaining very high levels of engine e ciency. This has been confirmed in more recent studies 9,10 .…”
Section: Introductionsupporting
confidence: 79%
“…The center of combustion, estimated online with the Rassweiler and Withrow method [10], was set to 368 • CA by closed-loop-control of the ignition angle. This value was chosen for all the experiments as it gives the highest efficiency (or maximum brake torque, respectively) and it ensured stable operation [11]. Figure 1 (right) provides a picture of the test-bench setup (engine and entire control unit) and Table 1 lists the main characteristics of the experimental setup.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the thermal efficiency is increased due to the extended expansion stroke relative to the compression stroke [17]. If a suitable exhaust aftertreatment system is used, lean combustion concepts with pre-chamber or pilot ignition lead to a significant increase of the thermal efficiency [18,19] and efficiency levels of above 45% are achievable for passenger car size engines [20]. Cooled exhaust gas recirculation in combination with variable compression ratios allows for improvement of the thermal efficiency, while the formation of emissions such as nitrogen-oxides (NO x ) and hydrocarbons (HC) are decreased [21].…”
Section: Introductionmentioning
confidence: 99%